(untitled) (Medical Forum Monthly, 2024)
Aims of Study: The purpose of this study was to understand the malarial situation in Punjab, Pakistan. Place and Duration of Study: In this study, the data was collected from different health facilities, malaria control programme offices, reference laboratories and field stations of 91 districts from 2005 to 2009. Materials and Methods: The data of past five years (2005-2009) from health facilities, malaria control programme offices, reference laboratories and field stations was collected. An excel databank was created and analysis was done by using SPSS. Out of the total of 123 districts, 91 districts (86.7%) were endemic for malaria in Pakistan. Balochistan and FATA (Federally Administered Tribal Areas) had highest malaria incidence, while Sind and KPK (Khyber Pakhtoon Khah) had moderate. The lowest malaria incidence was confined to Punjab and AJK (Azad Jammu Kashmir). In Punjab the maximum API (Annual Parasitic Incidence) was noted 0.04 in 2005 and 0.05 in 2009. The incidence of cases in south Punjab was more than central and north Punjab, 82% of indigenous cases were of Plasmodium vivax, 18% were of P.falciparum, P.ovale & P.malariae or mix infection was not reported. In Punjab malaria has reduced significantly (p=0.028) and fully qualifies the embarkation of malaria elimination strategy. Prioritizing to target P.falciparum first and subsequently eliminate the P.vivax malaria. KAP (Knowledge, Attitudes and Practices) study is required before initiating malaria elimination in Punjab, Pakistan.